Hydrodynamics of vegetated channels - Nepf, Heidi M. (Journal of hydraulic research, 2012)
This paper highlights some recent trends in vegetation hydrodynamics, focusing on conditions within channels and spanning spatial scales from individual blades, to canopies or vegetation patches, to the channel reach. At the blade scale, the boundary layer formed on the plant surface plays a role in controlling nutrient uptake. Flow resistance and light availability are also influenced by the reconfiguration of flexible blades. At the canopy scale, there are two flow regimes. For sparse canopies, the flow resembles a rough boundary layer. For dense canopies, the flow resembles a mixing layer. At the reach scale, flow resistance is more closely connected to the patch-scale vegetation distribution, described by the blockage factor, than to the geometry of individual plants. The impact of vegetation distribution on sediment movement is discussed, with attention being paid to methods for estimating bed stress within regions of vegetation. The key research challenges of the hydrodynamics of vegetated channels are highlighted.